2005
DOI: 10.2223/jped.1399
|View full text |Cite
|
Sign up to set email alerts
|

Pediatricians and the external causes of morbidity and mortality

Abstract: Contudo, a produção científica nacional nessa área ainda é muito tímida. Uma busca realizada nos arquivos do Jornal de Pediatria disponíveis on-line (utilizando os termos injúria, trauma, traumatismo, acidente, violência, maus-0021-7557/05/81-05-Supl/S119

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2011
2011
2011
2011

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 22 publications
0
2
0
Order By: Relevance
“…Therefore, lack of knowledge is even more alarming because of the possible preventive measures that should be taken, but are not. Studies about it in the Brazilian literature are scarce considering the relevance of this topic (14) . Several studies that included vehicles involved in crashes found that the correct use of restraints, as well as the transportation of children in the rear seat, significantly reduces the risk of death and injuries due to accidents (5,15,25) .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, lack of knowledge is even more alarming because of the possible preventive measures that should be taken, but are not. Studies about it in the Brazilian literature are scarce considering the relevance of this topic (14) . Several studies that included vehicles involved in crashes found that the correct use of restraints, as well as the transportation of children in the rear seat, significantly reduces the risk of death and injuries due to accidents (5,15,25) .…”
Section: Discussionmentioning
confidence: 99%
“…As a result of inadequate transportation, children may have major trauma in crashes. There are potentially greater chances of multiple organ injury and a greater incidence of closed trauma, as well as greater potential risk of ejection from the vehicle, which makes head trauma the main cause of death in these cases (14,26) . There is also evidence that, to reduce morbidity and mortality in traffic accidents, all passengers should be using restraints correctly (25) .…”
Section: Discussionmentioning
confidence: 99%